The Role of Mechanical Force and ROS in Integrin-Dependent Signals - Zeller, Kathrin S. (Public Library of Science, 2013)
Cells are exposed to several types of integrin stimuli, which generate responses generally referred to as “integrin signals”, but the specific responses to different integrin stimuli are poorly defined. In this study, signals induced by integrin ligation during cell attachment, mechanical force from intracellular contraction, or cell stretching by external force were compared. The elevated phosphorylation levels of several proteins during the early phase of cell attachment and spreading of fibroblast cell lines were not affected by inhibition of ROCK and myosin II activity, i.e. the reactions occurred independently of intracellular contractile force acting on the adhesion sites. The contraction-independent phosphorylation sites included ERK1/2 T202/Y204, AKT S473, p130CAS Y410, and cofilin S3. In contrast to cell attachment, cyclic stretching of the adherent cells induced a robust phosphorylation only of ERK1/2 and the phosphorylation levels of the other investigated proteins were not or only moderately affected by stretching. No major differences between signaling via α5β1 or αvβ3 integrins were detected. The importance of mitochondrial ROS for the integrin-induced signaling pathways was investigated using rotenone, a specific inhibitor of complex I in the respiratory chain. While rotenone only moderately reduced ATP levels and hardly affected the signals induced by cyclic cell stretching, it abolished the activation of AKT and reduced the actin polymerization rate in response to attachment in both cell lines. In contrast, scavenging of extracellular ROS with catalase or the vitamin C analog Asc-2P did not significantly influence the attachment-derived signaling, but caused a selective and pronounced enhancement of ERK1/2 phosphorylation in response to stretching. In conclusion, the results showed that “integrin signals” are composed of separate sets of reactions triggered by different types of integrin stimulation. Mitochondrial ROS and extracellular ROS had specific and distinct effects on the integrin signals induced by cell attachment and mechanical stretching.